Pengembangan Media Pembelajaran Flashcard pada Mata Pelajaran Biologi Pokok Bahasan Bioteknologi Kelas X SMA Negeri 5 Kota Samarinda - Saputra, Apri Prananda; Akhmad, Akhmad; Nasution, Ruqoyyah; Purwati, Sri; Makkadafi, Suparno Putera; Serena, Nelda Anasthasia (Biocaster : Jurnal Kajian Biologi, 2025)
The low activeness of students in learning biology is still a common problem found in various educational units, one of which is at SMA Negeri 5 Samarinda City. Biology learning at SMA Negeri 5 Kota Samarinda still faces obstacles in terms of student activeness. So that there needs to be a solution in the form of learning media that is attractive to students. This study aims to develop flashcard learning media in the form of educational cards in biology subjects on the subject of biotechnology and determine the feasibility of the media. The method used is research and development (Research and Development) with the ADDIE model which consists of 5 stages of research. Based on the results of the needs. analysis conducted at SMA Negeri 5 Kota Samarinda, teachers need flashcard learning media by 74%. Meanwhile, students need flashcard learning media by 81% of class X-3 and 82% of class X-7. This development research produces a product in the form of flashcard learning media in the form of a double-sided educational card that is feasible to use based on the assessment of: 1) media expert validators obtained a score of 78.33%; and 2) material expert validators obtained a score of 95.71%. Meanwhile, the response of students in the small-scale trial obtained a score of 80.39% and the response of students in the large-scale trial obtained a score of 81.11%. Meanwhile, the teacher's response obtained a score of 90%. So it can be concluded that the flashcard learning media developed is suitable for use and gets a positive response from students and teachers.